1275. Factors Associated with Patient-Provider Discussions about Preexposure Prophylaxis Among Young Men Who Have Sex with Men in Washington, DC - Ware, Chelsea (Open Forum Infect Dis, 2019)
BACKGROUND: The CDC estimates that 1.2 million people in the United States are eligible for HIV pre-exposure prophylaxis (PrEP). However, only about 120,000 people have received PrEP prescriptions through 2017. Healthcare providers’ (HCP) willingness to engage patients in discussions regarding sexual health, including PrEP, is integral to increasing PrEP uptake in the United States. Our objective was to identify factors associated with patients having discussions about PrEP with their HCP. METHODS: Men who have sex with men (MSM) aged 16–25 in the Washington, DC metro area recruited from the community completed a web-based survey in 2016 about their perceptions of and experiences with PrEP. We used multivariable logistic regression to calculate adjusted odds ratios (aOR) for associations between sociodemographic characteristics (including: age, race/ethnicity, insurance, student/employment status, education, income, living arrangements, social support, depressive symptoms) and patient-provider discussions, including willingness to have or ever having a discussion about PrEP. RESULTS: Among 239 MSM, 51% were Black, 25% were White, and 16% were Hispanic. 154 participants (65%) were willing to ask a HCP about PrEP without their HCP bringing it up. 159 participants (67%) reported that a HCP had never talked to them about PrEP, although 100 of the 159 (63%) expressed interest in discussing PrEP with a HCP. Participants aged <21 were less willing to ask a HCP about PrEP (aOR: 0.49, 95% CI 0.28–0.85) and insured participants were more willing to ask their HCP about PrEP (aOR: 3.64, 95% CI 1.42–9.33). In multivariable analyses, no sociodemographic characteristics were associated with having talked to a HCP about PrEP, and among those who had never talked to a HCP about PrEP, no characteristics were associated with wanting to do so. CONCLUSION: There is a need to increase PrEP uptake in populations at high risk for HIV exposure. While MSM >21 and those with health insurance were more willing to ask their HCP about PrEP, there were no other differences across multiple demographic groups. Our study suggests that a wide PrEP engagement strategy that encourages HCPs to address PrEP with their patients regardless of their demographics would be beneficial to increase PrEP uptake. [Image: see text] [Image: see text] [Image: see text] [Image: see text] DISCLOSURES: All authors: No reported disclosures.